The Haralds of Hydrogen The Economic Sectors Driving the Hydrogen Economy in Europe - de Klerk Wolters, Floris Jacobus Adrianus (eCahiers de l'Institut, 2022)
This paper analyses membership data from 39 hydrogen associations to understand which economic sectors support the hydrogen transition in Europe, and why. It finds support from manufacturers of motor vehicles, chemicals, (electronic and electrical) machinery, electricity and gas companies, companies working in transport and storage (including ports), oil and gas companies, and many professional, scientific, and technical companies. Chemicals manufacturers and natural gas utilities stand out in their interest, as well as SMEs working in the value chain of hydrogen and fuel cell products. Registrations are clustered in the North Sea Region and the Iberian Peninsula, with many fewer registrations in Italy and Eastern Europe (including Russia). Motives for supporting the hydrogen transition include sales and market growth, rising CO2 emissions costs, regulatory and public pressure to decarbonise, avoiding stranded assets, diversification, investor concerns about the long-term profitability of carbon-intensive sectors, and sector-specific concerns. We extend our heartfelt thanks to the Vahabzadeh Foundation for financially supporting the publication of best works by young researchers of the Graduate Institute, giving a priority to those who have been awarded academic prizes for their master's dissertations.